ASSESSMENT OF THE PREVALENCE OF INFLAMMATORY DISEASES OF THE HARD AND SOFT TISSUES OF THE ORAL CAVITY IN CONTACT SPORT ATHLETES (American Journal of Interdisciplinary Research and Development, 2022)
The purpose of this study was to study the relationship between oral diseases and functional disorders of the body of athletes engaged in contact sports against the background of intensive physical training. 64 professional athletes of various levels of fitness engaged in contact (wrestling, boxing) sports in the pre-competitive and competitive periods of the training process at the age of 16-24 years with a duration of sports experience - 2-5 years and 14 practically healthy persons not engaged in sports of the highest achievements were examined. The dental status was studied and a survey of all study participants was conducted using a developed specialized card and data were obtained on sports injuries of the maxillofacial region, as well as on the experience of using protective sports mouthguards. The highest prevalence of inflammatory diseases of the hard and soft tissues of the oral cavity was detected in representatives of contact sports such as boxing.